2021
DOI: 10.18632/aging.202580
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the association between brain atrophy, hypometabolism, and cognitive decline in Alzheimer’s disease: a PET/MRI study

Abstract: Glucose metabolism reduction and brain volume losses are widely reported in Alzheimer’s disease (AD). Considering that neuroimaging changes in the hippocampus and default mode network (DMN) are promising important candidate biomarkers and have been included in the research criteria for the diagnosis of AD, it is hypothesized that atrophy and metabolic changes of the abovementioned regions could be evaluated concurrently to fully explore the neural mechanisms underlying cognitive impairment in AD. Twenty-three … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 60 publications
0
7
0
Order By: Relevance
“…Mitochondrial dysfunction, which is associated with increased oxidative stress, is a major driving force of the progression of Alzheimer’s, Parkinson’s, and Huntington’s disease, as well as several other neurological disorders ( Lin and Beal, 2006 ; Austad et al, 2021 ). The progressive loss of glucose metabolism is also a prevalent feature of neurodegenerative disease, as indirectly shown by FDG-PET and MRI imaging, as well as measurement of concentrations of lactate, pyruvate, and TCA cycle metabolites in patient cerebrospinal fluid ( Parnetti et al, 1995 ; Redjems-Bennani et al, 1998 ; Buckner et al, 2005 ; Edison et al, 2007 ; Schroeter et al, 2009 ; La Joie et al, 2012 ; Liguori et al, 2016 ; Marchitelli et al, 2018 ; Chen et al, 2021 ). Therefore, a better understanding of the metabolic dysfunction that occurs in the brain during neurodegenerative disease progression is needed, at both the mitochondrial level, as well as upstream regarding the use of major metabolites such as glucose.…”
Section: Discussionmentioning
confidence: 99%
“…Mitochondrial dysfunction, which is associated with increased oxidative stress, is a major driving force of the progression of Alzheimer’s, Parkinson’s, and Huntington’s disease, as well as several other neurological disorders ( Lin and Beal, 2006 ; Austad et al, 2021 ). The progressive loss of glucose metabolism is also a prevalent feature of neurodegenerative disease, as indirectly shown by FDG-PET and MRI imaging, as well as measurement of concentrations of lactate, pyruvate, and TCA cycle metabolites in patient cerebrospinal fluid ( Parnetti et al, 1995 ; Redjems-Bennani et al, 1998 ; Buckner et al, 2005 ; Edison et al, 2007 ; Schroeter et al, 2009 ; La Joie et al, 2012 ; Liguori et al, 2016 ; Marchitelli et al, 2018 ; Chen et al, 2021 ). Therefore, a better understanding of the metabolic dysfunction that occurs in the brain during neurodegenerative disease progression is needed, at both the mitochondrial level, as well as upstream regarding the use of major metabolites such as glucose.…”
Section: Discussionmentioning
confidence: 99%
“…The association between brain volume, brain atrophy, and cognitive function has been extensively investigated in studies involving Parkinson’s disease, multiple sclerosis, Alzheimer’s disease, and the general population; yet, few studies have explored the relationship between CI and white matter lesions, as well as brain atrophy, in CKD patients [ 28 , 35 , 36 , 37 , 38 ]. Yeh et al [ 39 ] found a significant correlation between attention and executive function and white matter lesions, but no correlation with brain atrophy.…”
Section: Relationship Between Brain Atrophy and CI In Ckd Patientsmentioning
confidence: 99%
“…In several studies, glucose hypometabolism follows a similar anatomical progression to the Braak stages of AD, and Tau pathology seen in Progressive Supranuclear Palsy and Corticobasal Degeneration [41][42][43] . However, it is noted that variations in the age of disease onset may have caused discrepancies between studies [44][45][46][47] . Furthermore, Tau pathology and glucose hypometabolism were shown to correlate with cognitive decline [48] .…”
Section: Metabolic Deficits and Tau Pathologymentioning
confidence: 99%